2022
DOI: 10.1111/mmi.14999
|View full text |Cite
|
Sign up to set email alerts
|

The MerR‐family regulator NmlR is involved in the defense against oxidative stress in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae has to cope with the strong oxidant hypochlorous acid (HOCl), during host–pathogen interactions. Thus, we analyzed the global gene expression profile of S. pneumoniae D39 towards HOCl stress. In the RNA‐seq transcriptome, the NmlR, SifR, CtsR, HrcA, SczA and CopY regulons and the etrx1‐ccdA1‐msrAB2 operon were most strongly induced under HOCl stress, which participate in the oxidative, electrophile and metal stress response in S. pneumoniae. The MerR‐family regulator NmlR harbors a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
0
10
1
Order By: Relevance
“…Furthermore, MerA/RclA enzymes are highly conserved in bacteria colonizing epithelial surfaces, including the phyla Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria (Derke et al, 2020), but their role remains to be demonstrated. Unlike MerA and RclA, which are highly inducible in S. aureus and E. coli in response to reactive (pseudo-)halogen species (present study, Loi et al, 2018a;Parker et al, 2013), via the redox-sensitive regulators HypR and RclR, respectively, transcription of har was not elevated in S. pneumoniae after HOCl stress (Fritsch et al, 2022). In support of this, har (SPD_1415) is not located adjacent to a putative regulatory gene in the S. pneumoniae genome, as indicated by the KEGG pathway database.…”
Section: S Aureuscontrasting
confidence: 50%
See 1 more Smart Citation
“…Furthermore, MerA/RclA enzymes are highly conserved in bacteria colonizing epithelial surfaces, including the phyla Actinobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Proteobacteria (Derke et al, 2020), but their role remains to be demonstrated. Unlike MerA and RclA, which are highly inducible in S. aureus and E. coli in response to reactive (pseudo-)halogen species (present study, Loi et al, 2018a;Parker et al, 2013), via the redox-sensitive regulators HypR and RclR, respectively, transcription of har was not elevated in S. pneumoniae after HOCl stress (Fritsch et al, 2022). In support of this, har (SPD_1415) is not located adjacent to a putative regulatory gene in the S. pneumoniae genome, as indicated by the KEGG pathway database.…”
Section: S Aureuscontrasting
confidence: 50%
“…Unlike MerA and RclA, which are highly inducible in S. aureus and E. coli in response to reactive (pseudo‐)halogen species (present study, Loi et al, 2018a; Parker et al, 2013), via the redox‐sensitive regulators HypR and RclR, respectively, transcription of har was not elevated in S. pneumoniae after HOCl stress (Fritsch et al, 2022). In support of this, har ( SPD_1415 ) is not located adjacent to a putative regulatory gene in the S. pneumoniae genome, as indicated by the KEGG pathway database.…”
Section: Discussionmentioning
confidence: 52%
“…Given the physiological significance of HOX exposure during infection, research in this field is rapidly evolving even though we are still far away from understanding the full picture of HOX defenses in bacteria. The bacterial response and defense strategies are expected to be critical for their ability to survive the immune cell attack, as reported by several recent studies ( Sultana et al, 2022 ; Fritsch et al, 2023 ; Foik et al, 2022 preprint). Moreover, independent studies confirmed that the presence of functional oxidative stress defense systems positively affects pathogen colonization in the host, emphasizing their importance for pathogenesis ( Peng et al, 2020 ; Dahl et al, 2017 ; Hryckowian and Welch, 2013 ; Bessaiah et al, 2019 ).…”
Section: Future Prospectsmentioning
confidence: 83%
“…HOCl-sensing transcription factors also play an important role for the activation of HOCl defense systems in Gram-positive pathogens ( Beavers and Skaar, 2016 ) . A recently studied example is the Streptococcus pneumoniae 1-Cys-type regulator NmlR, which forms intermolecular disulfide bonds upon oxidation of its redox-sensitive cysteine residue but remains bound to the promoter DNA regardless of its oxidation state ( Fritsch et al, 2023 ). Oxidized NmlR presumably distorts the promoter DNA, resulting in improved RNA polymerase binding and increased adhC transcript levels ( Fig.…”
Section: A Year At the Forefront Of Bacterial Defense Systems Against...mentioning
confidence: 99%
“…Comparative genomics suggests that this system is conserved in pathogenic Neisseria [ 62 , 63 ]. NmlR is present in several other pathogenic bacteria that colonize the mucosae of their hosts, such as Haemophilus influenzae [ 32 , 35 ] and Streptococcus pneumoniae [ 64 ]. NmlR is involved in regulating the response to ROS, RNS, and/or RCS, depending on the organism.…”
Section: Copper Homeostasis Controlled By Reactive Nitrogen Species: ...mentioning
confidence: 99%